Technologically advanced running shoes reduce biomechanical factors of running related injury risk - Hyunji Kim; Jooeun Ahn (Scientific Reports)
Abstract Recent footwear technology has led to the development of technologically advanced running shoes (TARS), which improve running performance. However, the effect of TARS on biomechanical risk factor remains unclear. This study compares the effects of TARS with those of conventional cushioned shoes (CON) and minimalist shoes (MIN) on running biomechanics and biomechanical risk factors. We recruited 15 recreational runners, measured their ventilation threshold speeds and habitual strike angles, collected kinematic data and ground reaction forces across shoe conditions, and estimated joint reaction force and muscle force through inverse dynamic analysis. Results show that TARS significantly alter landing patterns by shifting runners toward a forefoot/midfoot strike patterns (mean strike angle decreased by 4.17° compared to CON) and reducing subtalar eversion during loading phase. While MIN increase peak ankle joint reaction force by 3.07 body weight (BW) compared to CON, TARS reduce it by 1.84 BW. TARS also decrease peak soleus and peroneus longus forces by 1.10 BW and 0.43 BW respectively, without increasing demands on any joint. These results suggest that TARS provide distinct biomechanical characteristics that reduce certain mechanical loads associated with running injuries. Our findings further suggest a need for reevaluating footwear classification methods and embracing technological advancements in running shoe design for potentially safer and more efficient running.